Collection and Use of Information by Counter-Intelligence in the Context of Human Rights Protection - Dimich, Antonina; Petrov, Valentyn; Sliusarchuk, Ivan; Mishchyshyn, Nataliia; Fornolyak, Valentyna (The Age of Human Rights Journal, 2022)
Obtaining complete and reliable information during counter-intelligence activities is very critical. The extraction, analytical processing, and use of information regarding signs and facts of intelligence, terroristic, and other activities of special services of foreign states, as well as organisations, individual groups, and individuals to the detriment of the state security of Ukraine is legally established as its main task. One of the main tasks of intelligence and counter-intelligence is to collect information in the interests of national security on the facts and signs of activities that threaten the sovereignty, territorial integrity, and constitutional order of the state, that is, its main system-forming component, using all possible sources. The purpose of such information collection is to assist the executive branch of government in developing internal and external policy, as well as to develop strategic and tactical decisions in the implementation of national policy. The purpose of this study was to identify the problems of collecting and using information by counter-intelligence, to develop a strategy to overcome such problems, and to investigate the legal principles of protecting human rights in the process of this activity. The results of the study will contribute to the development of the theory of national security, the obtained definition of the legal regime for collecting and using information about an individual or legal entity regarding which counter-intelligence actions are performed, will assist intelligence and counter-intelligence units in ensuring the protection of human rights during such activities.